2016
DOI: 10.1053/j.seminoncol.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing old drugs to chemoprevention: the case of metformin

Abstract: Multiple epidemiologic studies have documented an association between the anti-diabetic agent metformin and reduced cancer incidence and mortality. However, this effect has not been consistently demonstrated in animal models or more recent epidemiological studies. The purpose of this paper is to examine metformin's chemopreventive potential by reviewing relevant mechanisms of action, preclinical evidence of efficacy, updated epidemiologic evidence after correction for potential biases and confounders, and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 67 publications
1
57
0
Order By: Relevance
“…It also exemplifies the targeting of the obesity–diabetes–physical activity–energy balance axis, disruption of which by onset of the metabolic syndrome is associated with risk for certain cancers [6770]. Observational studies have shown metformin use by diabetics to correlate with reduced incidence of overall cancer, specific cancers (pancreatic, hepatocellular, colorectal, lung , and breast cancers [71]), and cancer mortality [7275]. However, results from observational studies are not consistent [73,76,77].…”
Section: Chemoprevention: Using Drugs and Nutrients To Decrease Cancementioning
confidence: 99%
“…It also exemplifies the targeting of the obesity–diabetes–physical activity–energy balance axis, disruption of which by onset of the metabolic syndrome is associated with risk for certain cancers [6770]. Observational studies have shown metformin use by diabetics to correlate with reduced incidence of overall cancer, specific cancers (pancreatic, hepatocellular, colorectal, lung , and breast cancers [71]), and cancer mortality [7275]. However, results from observational studies are not consistent [73,76,77].…”
Section: Chemoprevention: Using Drugs and Nutrients To Decrease Cancementioning
confidence: 99%
“…Recently metformin is being repurposed as an antitumor drug due to epidemiological findings revealing an association between decreased incidence of pancreatic cancer and metformin use in diabetic individuals. (3, 4) However, at typical antidiabetic doses, the bioavailability of metformin and/or its uptake by cancer cells is probably too low to exert its antitumor effects in humans, although singificant antitumor activity was reported in the rodent models, at comparable plasma concentrations. (5, 6) It appears that the antineoplastic activity of metformin in humans will require much higher concentrations of the drug in the serum than what is typically administered in diabetics treated with metformin.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge is beginning to be translated into clinical applications in the development of personalized chemotherapeutic regimens based on in vitro testing incorporating elements of the patient's tumor microenvironment (25). This new understanding is also shaping primary prevention strategies that promote a cancer-resistant extracellular environment, such as aspirin for colon cancer and metformin for breast cancer (26,27). Although these strategies so far have mostly targeted the biochemical aspects of the extracellular "milieu," such as locally released cytokines and growth factors (23), there is also a growing interest in biophysical factors within connective tissue, including extracellular matrix stiffness, alignment, and porosity, that may influence cancer growth (28)(29)(30).…”
Section: Importance Of Connective Tissue In Cancer Biologymentioning
confidence: 99%